Aflatoxin and liver cancer - Santos, Jefferson Andrade dos (Pesquisa Agropecuaria Brasileira, 2024)
The author reviews the principal animal and human micotoxicosis and focalizes the problem of aflatoxin with special emphasis on case history, pathogenesis and prophylaxis. The relationship between aflatoxin and epizootic cancer studied in rabbits is shown, besides an attempt to establish a correlation between aflatoxicosis and certain primary liver tumors of animals and man.